(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
Groundwater is one of the most important sources of freshwater and plays a vital role in sustaining and supporting economic development. Although protecting and preserving groundwater resources is challenging, it is essential to ensure their long-term availability and quality. The "DRASTIC" model is among the most widely used methods for evaluating groundwater vulnerability to contamination. This model assesses groundwater’s susceptibility to pollution based on the hydrogeological characteristics of aquifers, soil, and geological formations. Since 1987, the DRASTIC approach has been adopted by the United States Environmental Protection Agency (EPA) as a standard tool for groundwater vulnerability assessment. This study aims to evaluate the potential for groundwater contamination in Mosul city using the DRASTIC model integrated with Geographic Information Systems (GIS) techniques. The analysis was conducted using data collected from 26 wells provided by the Ministry of Water Resources, the General Authority for Groundwater in Mosul, the Groundwater Directorate, and the Geology and Drilling Department. Vulnerability maps were generated to identify areas at varying levels of contamination risk. The results indicate that the study area can be classified into four groundwater vulnerability zones: low, moderate, high, and very high. Most of the study area falls within the low-vulnerability category, with DRASTIC index values ranging from 1 to 100. Moderate vulnerability ranges from 101to 119, while high vulnerability ranges from 120 to 200. Aeras classified as very highly vulnerable, with DRASTIC index values exceeding 200, constitute only a small part of the study area, accounting for approximately 2.67% of the total area. To reduce pollution risks, preventive measures must be taken in vulnerable zones before starting industrial or agricultural activities.